Cytotoxicity and mutagenicity assessment of organomodified clays potentially used in food packaging. Issue 6 (September 2015) - Maisanaba, Sara; Prieto, Ana I.; Pichardo, Silvia; Jordá-Beneyto, María; Aucejo, Susana; Jos, Ángeles
Highlights Clay1 was not cytotoxic to HUVEC, although potential mutagenicity was found. Clay2 produced cytotoxicity in endothelial cells but no mutagenicity was recorded. CNa+ was not cytotoxic neither mutagenic. C30B showed positive results in cytotoxic and mutagenic studies.